Glutathione peroxidase and catalase enzyme gene polymorphisms in profound congenital hearing loss* - Tunç, Orhan; Baysal, Elif; Oğuzkan Balcı, Sibel; Mumbuç, Semih; Güngör Tunç, Nihal; Pehlivan, Sacide; Kanlıkama, Muzaffer (ENT Updates, 2017)
Objective: The aim of this study was to search the codon 200 polymorphism on the glutathione peroxidase 1 gene (GPX1) and A/T changes on the promoter region of the catalase gene (CAT) in cochlear implant patients with congenital profound hearing loss. Methods: Sixty-five cochlear implant patients with congenital hearing loss and 100 age- and gender-matched healthy volunteers were evaluated between 2011 and 2013. Genomic DNA was extracted from peripheral blood samples by using the salting out procedure. The T/A polymorphism in the promoter region of the CAT gene (rs7943316) and GPX1 gene codon 200 proline to leucine substitution (rs1050450) were determined by polymerase chain reaction and restriction fragment length polymorphisms. Results: No statistically significant difference was found in CC and CT genotypes in codon 200 on GPX1 (CC, p=0.10; CT, p=0.48) However, there was a statistically significant difference in the TT genotype (p=0.04). In the CAT promoter region, there was no statistically significant difference between the patients and control groups (AA, p=0.41; TA, p=0.16; TT, p=0.08). Conclusion: As a conclusion, the TT genotype on the GPX1 codon 200 may have a relationship with congenital profound sensorineural hearing loss.